2009
DOI: 10.2307/20650274
|View full text |Cite
|
Sign up to set email alerts
|

The Shoemaker's Children: Using Wikis for Information Systems Teaching, Research, and Publication

Abstract: This paper argues that Web 2.0 tools, specifically wikis, have begun to influence business and knowledge sharing practices in many organizations. Information Systems researchers have spent considerable time exploring the impact and implications of these tools in organizations, but those same researchers have not spent sufficient time considering whether and how these new technologies may provide opportunities for us to reform our core practices of research, review, and teaching. To this end, this paper calls f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
126
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 35 publications
0
126
0
3
Order By: Relevance
“…Web 2.0 technologies like wikis and social bookmarking have been used in previous research to develop a collaborative knowledgebase for a class Kane & Fichman, 2009). Agarwal and Ahmed (2013) used a wiki tool to help write test questions and found that this tool led to a student-centric and concept-centric learning experience.…”
Section: Social Learningmentioning
confidence: 99%
“…Web 2.0 technologies like wikis and social bookmarking have been used in previous research to develop a collaborative knowledgebase for a class Kane & Fichman, 2009). Agarwal and Ahmed (2013) used a wiki tool to help write test questions and found that this tool led to a student-centric and concept-centric learning experience.…”
Section: Social Learningmentioning
confidence: 99%
“…Other researchers have also made suggestions about how to use IT to support the review process (e.g., Mandaviwalla, Patnayakuni, & Schuff, 2008;Kane & Fichman, 2009;Hardaway & Scamell, 2012). However, when resorting to technology, one should consider the "business" rules of reviewing to be embedded in the technology and the role of technology in the larger system of publishing.…”
Section: Introductionmentioning
confidence: 99%
“…They are convinced that the adoption of social media technologies is responsible for ill social behavioral problems among users and, in particular, students (Galagan, 2010). While these instructors view social media technologies as a form of "behavioral menace to society", others (Kane & Fichman, 2009) view them as a viable tool for engaging students (Grosseck & Holotescu, 2008). In this paper, we focus on how to leverage Twitter to engage students with their course materials "in" and "out" of the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the spontaneous interaction patterns on microblogging services -such as Twitter provide a shared space for participants to collaboratively validate their mental model representations of the discussion topic (Holland, Holyoak, Nisbett, & Thagard, 1986). In response to calls for research in the IS discipline on appropriating SMTs tools in teaching (Kane & Fichman, 2009), we draw from engagement theory (Kearsley & Shneiderman, 1998) and social impact theory (Latane, 1981) to investigate how educators and students can leverage Twitter as an innovative tool to support engagement and learning.…”
Section: Introductionmentioning
confidence: 99%